Inovasi Pembelajaran Kimia: Implementasi Pembelajaran Kimia Berbasis Literasi Keagamaan Lintas Budaya Sebagai Alternatif Membangun Sikap Moderasi Beragama - Hidayati, Ririn Eva (Balai Diklat Keagamaan Surabaya, 2024)
This investigation aims to decide the implementation of chemistry learning based on cross-cultural religious literacy (CCRL). This research is a quantitative and qualitative descriptive research. This research design was carried out using the One Shoot Case Study method. The data collection technique used was observation of the implementation of learning, and a questionnaire to measure students' understanding and behavior of religious moderation. Based on data analysis, the results obtained were: The teacher has implemented chemistry learning based on cross-cultural religious literacy with agood category, student activity in applying personal, comparison, and collaboration competence is 12.5; 19.75 and 20.25% and evaluation, negotiation and communication skills of 14.5; 16 and 17%. Students' understanding and behavior of religious moderation is included in the very good category.